Periodontoprotective and cariesprofylactic effectS of cytoflavin and quertulin in rats with asiderotic anemia - Volovik, I. A.; Borisenko, A. V.; Levitsky, A. P. (Journal of Education, Health and Sport, 2017)
Aim: To carry out the comparative study of the effect of the preparations of cytoflavin and quertulin upon periodontium and blood system at asiderotic anemia (AsAn). Methods: The experiments were carried out with rats, kept to asiderotic diet (AsD). Cytoflavin (like a paste on white clay) and quertulin (like gel) were applied on gum during 21 days dosed at 0.5 ml per rat. The contents of erythrocytes, leucocytes, hemoglobin and lymphocytic index were determined in blood. The contents of lactate, pyruvate, activity of elastase, urease were estimated in gum. Results: At AsAn in blood the contents of erythrocytes, hemoglobin reduce, the considerable leucopenia is observed. In gum the activity of elastase, urease, the contents of pyruvate grows, the contents of lactate decreases. The applications of the paste with cytoflavin on gum reduce the activity of elastase, urease, contents of pyruvate and increase the contents of lactate. The same effect is achieved by quertulin, but the last one reduces the contents of lactate and partially restores the hematologic indices. Conclusion: At AsAn the hypoxia, dysbiosis and inflammation develop in periodontium, and the level of hemoglobin, erythrocytes and leucocytes reduces in blood. Cytoflavin and quertulin eliminate pathological phenomena in periodontium, but quertulin restores partially hematological indices.